استراتيجية ابن حزم في (طوق الحمامة): مقاربة نصية (The Strategies of Ibn Ḥazm in Ṭawq al-Ḥamāmah: A Textual Approach) - Abbas Bin Yahya عباس بن يحيى (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: إن إرث (ابن حزم) المتنوع يعكس شخصية متميزة، أثارت نقاشاً في زمنها واستمر إلى يومنا هذا. وقد مثل نص (طوق الحمامة) ونصوص المتن القرائي التي تشكلت حوله حقلاً ثرياً اتصل بمجالات معرفية مختلفة، ورغم أن هذه المحاولة تستفيد منها، إلا أنها تهدف في جوهرها إلى إنجاز قراءة تتجه إلى محاولة فهم استراتيجية ابن حزم في بناء المعنى في نص (الطوق)؛ ولهذا السبب فإن المدخل السيميائي ومستنده الإجرائي التأويلي هو أهم ما اعتمدته الدراسة، وقد انتهت إلى أن النص مبني على استدراج القارئ ضمن خريطته الخاصة التي شكّلها من موضوع (الحب)، فلم ينغلق ضمن أطر التحديدات والتفريعات العلمية والمنهجية، بل يبني شبكة من دلالات انطلاقا من سيمياء العنوان واستراتيجية السيرة الذاتية وأبعاد المكان. الكلمات المفتاحية: طوق الحمامة– المعنى– القارئ- السيرة الذاتية – الحب. Abstract: The legacy of Ibn Ḥazm consists of a very distinctive character which continuously stirs debates until today. The text The Ring of the Dove has managed to give rise to various other studies and texts which are relate to various aspects of knowledge. This study tries to uncover the various strategies employed by Ibn Ḥazm in constructing his concept and meaning this distinctive piece of work. Therefore, the semiological approach and its practical and explanatory method is the basis of this study. It is concluded that the text was constructed on the eventualization of the understanding of the concept of love in the minds of the readers. It was not restricted to the frameworks of knowledge and methodological definitions but was based on a network of meanings beginning from the semiology of the topics, the strategies of autobiography and the dimension of places. Keywords: Ring of the Dove– Meaning– Reader– Biography– Love. Abstrak: Sesungguhnya karya peninggalan Ibn Ḥazm yang pelbagai mencerminkan peribadi berbeza dan membangkitkan perbincangan yang berlarutan sehingga zaman sekarang. Sesungguhnya teks Ṭawq al-Ḥamāmah serta beberapa karya seangkatannya mewakili sebuah genre yang kaya dengan pelbagai bidang ilmu. Kajian ini pada asasnya bertujuan memahami strategi yang digunapakai oleh Ibn Ḥazm dalam pembinaan struktur pengertian dalan karya (al-Ṭawq). Dengan itu, kajian ini mengambil kaedah persimbolan yang bersandarkan kepada penafsiran dan mendapati bahawa topik karya ini berdasarkan kasih sayang. Ia tidak hanya berkisar pada pembahagian ilmu dan metodolgi sahaja, bahkan, membina rangkaian pengertian bertitik tolak daripada simbol dalam tajuk, strategi pengkajian latar belakang dan dimensi tempat. Kata kunci: Ṭawq al-Ḥamāmah– Pengertian– Khalayak Pembaca– Latar Belakang– Kasih Sayang.